78.3k views
0 votes
(3 × 2)^2 + 6 ÷ 3 × 2

User Afollestad
by
5.1k points

1 Answer

7 votes

For this case we have according to the order of algebraic operation PEMDAS that:

P: Operations within parentheses must be resolved first.

E: Exponentials

MD: Multiplication and division from left to right

AS: Addition and subtraction from left to right

Thus, simplifying the expression we have:


6 ^ 2 + 6 ÷ 3 × 2 =

36 + 6 ÷ 3 × 2 =


36 + 2*2 =\\36 + 4 =\\40

Answer:

40

User Kisuka
by
5.4k points